The Aquaeous Extract of Root Nodules Vigna radiata (rnVr) which Inoculated by Rhizobium as an Orally Available Anemia Therapeutic Candidate - Dewi Hidayati; Tutik Nurhidayati; Shinta Hartanto; N. Nurjannah (Indonesian Journal of Biotechnology, 2008)
The extract of root nodules Vigna radiata (rnVr) which inoculated by Rhizobium is considered beneficial as an orally available anemia therapeutic candidate, because it contain the leghemoglobin. The positive control mice (group I) were fed with the high nutrient pellet.The twelve mice (Mus musculus) was treated with the “taking rice pellet” that representing the low nutrient food for 21 days until they suffered anemia. Then, the anemia mice were treated orally with rnVr in different concentration groups:II. 0% III.33%; IV.67% and V.100%, respectively and fed with the “aking rice pellet”. After 14 days, the blood mice were collected from orbital sinus. The hemoglobin (Hb) concentration were analyzed by spectrophotometry and blood plasma profile protein were analyzed with electrophoresis (SDS-PAGE). All anemia mice that treated with rnVr showed the increasing of Hb and group that treated with 100% extract of rnVr could reach a normal Hb value, raising from 9.85 to 12.68 g/dL. There were observed the proteins which have molecule weight 36.5 and 35.7 kDa that indicated the existing erythropoietin. The increasing haemoglobin concentration and erythropoietin suggested if extract of rnVr could increasing red blood production and potential as an orally available anemia therapeutic candidate.